« Vous semez de la ciguë et prétendez voir mûrir des épis! » (Machiavel) : polar et anthropologie urbaine à Chicago à l’âge de la prohibition - Benoît TADIÉ (E-REA)
Starting from a few key works (in particular Frederic Thrasher’s The Gang, 1927, and W. R. Burnett’s Little Caesar, 1929), this article attempts to shed light on the epistemological affinities between the Chicago school of urban sociology and American urban crime fiction in the 1920s. Through a comparative study of these two corpuses, it suggests that these affinities result not from coincidence but from a common vision of the city. This, in particular, comes out in the similar treatment of urban crime, seen both as a narrative construction and as a historical, geographical and social phenomenon.